Pengaruh Penggunaan Magnet Eksternal dan variasi arus Pada Pengelasan TIG Terhadap Struktur Mikro, Kekerasan dan Kekuatan Tarik Baja Karbon Rendah : The Effect of Using External Magnets and Current Variations in TIG Welding on the Microstructure, Hardness and Tensile Strength of Low Carbon Steel - Paundra, Fajar; Rakha Yudanta, Faturrizky; muhyi, andul; Pujiyulianto, Eko; Budi Darsono, Febri (Universitas Pendidikan Ganesha, 2025)
External magnetic fields can improve the quality of TIG welding results. This research aims to determine the effect of external magnetic fields in the TIG welding process. The material used in this research is SS400 steel. The welding process uses TIG (Tungsten Inert Gas) with varying currents of 70 A, 80 A, 90 A and 100 A and uses additional 2 Neodymium external magnets. Testing of welding results in the form of macro, micro structure, Vickers hardness test and tensile test. The macro structure test results show several welding defects such as porosity, incomplete penetration, underfill and distortion. Meanwhile, the results of microstructure testing show that the base metal contains ferrite and pearlite structures. The HAZ section contains ferrite, pearlite and martensite types of structures. The highest tensile test results were found in TIG welding connections without using a magnet with a current of 100 A, namely 368.234 MPa. The highest hardness test results were found in TIG welding joints using a magnet with a current of 100 A, namely 176,712 HVN. The use of external magnets can produce large penetration during the welding process and produce good welded joints. On the other hand, this can have a negative impact on the welding results if the distance between the electric arc and the material is not correct, and the torch does not move according to the welding path.